A checklist of Chinese crickets (Orthoptera: Gryllidea) - He, Zhu-Qing (Zootaxa, 2018)
A checklist of Chinese crickets, including Taiwan, is offered. Presently 331 species or subspecies have been reported including true crickets, scale crickets, ant crickets and mole crickets belonging to 6 families, 16 subfamilies and 83 genera. Modicogryllus (Modicogryllus) maculatus (Shiraki, 1930) is moved to Comidoblemmus as C. maculatus (Shiraki, 1930) comb. nov. Velarifictorus (Velarifictorus) koshunensis (Shiraki, 1911) is moved to Turanogryllus as T. koshunensis (Shiraki, 1911) comb. nov. Qingryllus Chen Zheng, 1995 syn. is the junior synonym of Goniogryllus Chopard, 1936. Loxoblemmus angulatus Bey-Bienko, 1956 syn. is the junior synonym of Loxoblemmus appendicularis Shiraki, 1930. Cophogryllus kuhlgatzi Karny, 1908 syn. is the junior synonym of Teleogryllus (Brachyteleogryllus) occipitalis occipitalis (Serville, 1838). Velarifictorus (Velarifictorus) aspersus borealis Gorochov, 1985 syn. is the junior synonym of Velarifictorus (Velarifictorus) aspersus aspersus (Walker, 1869). Modicogryllus (Modicogryllus) latefasciatus (Chopard, 1933) syn. is the junior synonym of Velarifictorus (Velarifictorus) micado (Saussure, 1877). Velarifictorus (Velarifictorus) ornatus caudatus (Shiraki, 1930) syn. is the junior synonym of Velarifictorus (Velarifictorus) ornatus ornatus (Shiraki, 1911). Dianemobius nigrofasciatus (Matsumura, 1904) syn. is the junior synonym of Dianemobius fascipes (Walker, 1869). Polionemobius mikado (Shiraki, 1911) syn. is the junior synonym of Polionemobius taprobanensis (Walker, 1869). Vietacheta picea Gorochov, 1992, Oecanthus euryelytra Ichikawa, 2001, Oecanthus similator Ichikawa, 2001, Xabea levissima Gorochov, 1992, Pteronemobius (Pteronemobius) yezoensis (Shiraki, 1911), Metioche (Metioche) japonica (Ichikawa, 2001), Natula matsuurai Sugimoto, 2001 are the first records from China.